Tendon material properties vary and are interdependent among turkey hindlimb muscles - Matson, Andrew (Company of Biologists, 2012)
The material properties of a tendon affect its ability to store and return elastic energy, resist damage, provide mechanical feedback and amplify or attenuate muscle power. While the structural properties of a tendon are known to respond to a variety of stimuli, the extent to which material properties vary among individual muscles remains unclear. We studied the tendons of six different muscles in the hindlimb of Eastern wild turkeys to determine whether there was variation in elastic modulus, ultimate tensile strength and resilience. A hydraulic testing machine was used to measure tendon force during quasi-static lengthening, and a stress–strain curve was constructed. There was substantial variation in tendon material properties among different muscles. Average elastic modulus differed significantly between some tendons, and values for the six different tendons varied nearly twofold, from 829±140 to 1479±106 MPa. Tendons were stretched to failure, and the stress at failure, or ultimate tensile stress, was taken as a lower-limit estimate of tendon strength. Breaking tests for four of the tendons revealed significant variation in ultimate tensile stress, ranging from 66.83±14.34 to 112.37±9.39 MPa. Resilience, or the fraction of energy returned in cyclic length changes was generally high, and one of the four tendons tested was significantly different in resilience from the other tendons (range: 90.65±0.83 to 94.02±0.71%). An analysis of correlation between material properties revealed a positive relationship between ultimate tensile strength and elastic modulus (r(2)=0.79). Specifically, stiffer tendons were stronger, and we suggest that this correlation results from a constrained value of breaking strain, which did not vary significantly among tendons. This finding suggests an interdependence of material properties that may have a structural basis and may explain some adaptive responses observed in studies of tendon plasticity.